AT1R Regulates Macrophage Polarization Through YAP and Regulates Aortic Dissection Incidence - Wang, Xinhao; Zhang, Hongpeng; Ge, Yangyang; Cao, Long; He, Yuan; Sun, Guoyi; Jia, Senhao; Ma, Airong; Liu, Jie; Rong, Dan; Guo, Wei (Frontiers in Physiology, 2021)
Abstract: Aortic dissection (AD) is one of the most fatal cardiovascular emergency. At the anatomical level, AD occurs due to the formation of intimal tears. However, the molecular mechanism underlying this phenomenon remains unknown. Angiotensin II (Ang II) is a important effector in the development of cardiovascular disease that acts through binding to angiotensin type 1 receptor (AT1R). Yes-associated protein (YAP) was recently recognized as a key protein in macrophage activation. To determine whether AT1R and YAP are involved in macrophage-induced endothelial cell (EC) inflammation and AD incidence, we co-cultured THP-1 cells and HAECs in transwell chambers under different culture conditions and apply different conditions to the AD mice model. The results showed that Ang II promoted macrophage M1 polarization and adhesion, upregulated YAP phosphorylation, and induced EC injury that was related to increased levels of multiple pro-inflammatory chemokines. Blocking AT1R function pharmacologically or by transfection with AT1R siRNA can reduce the pro-inflammatory effect induced by Ang II. In addition, siRNA knock down of YAP expression further aggravated the pro-inflammatory effects of Ang II. Treatment with ARB effectively alleviated these pro-inflammatory effects. In the mice AD model, ARB effectively reduced the incidence of AD in mice, decreased M1 macrophages infiltration and AT1R content in the aortic wall and increased the tissue content of YAP. We found that AT1R induces YAP phosphorylation through binding to Ang II, and further promotes macrophage M1 polarization and adhesion to ECs. ARB reduces the incidence of AD in mice and affect macrophage polarization in mice aorta.